1999
DOI: 10.1029/1999jd900062
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of UV radiation at the Earth's surface from TOMS‐measured UV‐backscattered radiances

Abstract: Abstract. Daily global maps of monthly integrated UV-erythemal irradiance (290-400 nm) at the Earth's surface are estimated using the ozone amount, cloud transmittance, aerosol amounts, and surface reflectivity from the solar UV radiation backscattered from the Earth's atmosphere as measured by the total ozone mapping spectrometer (TOMS) and independently measured values of the extraterrestrial solar irradiance. The daily irradiance values at a given location show that short-term variability (daily to annual) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
241
1
8

Year Published

2000
2000
2012
2012

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 227 publications
(285 citation statements)
references
References 35 publications
9
241
1
8
Order By: Relevance
“…When the effects of cloud cover are included in the zonally averaged annual exposure estimate, based on the TOMS reflectivity measurements [Herman et al, 1996[Herman et al, , 1999Krotkov et al, 1999], the results are substantially the same (Figure 3). There are small percent differences caused by cloud cover variability between successive years that are less than the QBO effect.…”
Section: Annual Variability Of Uv-b Exposuresupporting
confidence: 51%
See 1 more Smart Citation
“…When the effects of cloud cover are included in the zonally averaged annual exposure estimate, based on the TOMS reflectivity measurements [Herman et al, 1996[Herman et al, , 1999Krotkov et al, 1999], the results are substantially the same (Figure 3). There are small percent differences caused by cloud cover variability between successive years that are less than the QBO effect.…”
Section: Annual Variability Of Uv-b Exposuresupporting
confidence: 51%
“…UV-A irradiances (320-400 nm) are not significantly affected by ozone changes because of their small ozone absorption coefficients ax. After the solar zenith angle the second largest cause of daily variability, seasonal variability, and geographic distribution of UV irradiance is from clouds [Herman et al, 1999]. Analysis of the ozoneamount time series Herman et al, 1991] has shown that the major persistent sources of ozone variability are the annual cycle, the 2.3 year quasi-biennial oscillation cycle (QBO) [e.g., Bowman [1989], and the 11.5 year solar cycle [Hood, 1997; Zerefos et al, 1997; Calvo et al, 1995, and references therein].…”
Section: Introductionmentioning
confidence: 99%
“…The primary data set used for the current analysis was the DNA-weighted UV-B radiation exposure map obtained by using the Total Ozone Mapping Spectrometer (TOMS). 20,21 TOMS is a spacebased instrument that yields UV data for the entire country with a 1-degree ϫ 1.25-degree grid spacing. The July 1992 TOMS data, posted at the TOMS website, was used.…”
Section: Data Collectionmentioning
confidence: 99%
“…[7][8][9][10] For such cancers, mortality rates are about twice as high in the northeast as in the southwest and strongly inversely correlated with solar UVB radiation. 7,10,11 In addition, 6 types of cancer (breast, colon, endometrial, esophageal, ovarian and non-Hodgkin's lymphoma) are inversely correlated to both solar UVB radiation and rural residence in combination. 11 Urban residence is considered to reduce UVB exposure compared to rural residence in that it does not correlate with any other factor, such as lung cancer.…”
Section: Dear Sirmentioning
confidence: 99%
“…7,10,11 In addition, 6 types of cancer (breast, colon, endometrial, esophageal, ovarian and non-Hodgkin's lymphoma) are inversely correlated to both solar UVB radiation and rural residence in combination. 11 Urban residence is considered to reduce UVB exposure compared to rural residence in that it does not correlate with any other factor, such as lung cancer. For prostate cancer, the geographic variation is different.…”
Section: Dear Sirmentioning
confidence: 99%